Atroposelective Synthesis, Structure and Properties of a Novel Class of Axially Chiral N‐Aryl Quinolinium Salt. Issue 29 (24th March 2021) - Sweet, Jamie S.; Rajkumar, Sundaram; Dingwall, Paul; Knipe, Peter C.
Abstract: Inspired by naturally occurring molecules containing atropisomeric N + ‐C axes, we have developed a novel synthetic approach to generate a library of axially chiral N ‐aryl quinolinium salts. Enantiopurities up to 93 % ee were obtained via a four‐step route from commercially available precursors. Axial stereochemistry was controlled through an enantioselective ring‐closing Buchwald–Hartwig coupling reaction. The structure and properties of the salts were examined by X‐ray crystallography, DFT, UV‐Vis, and fluorescence spectroscopy, revealing high rotational barriers and solvatochromic behaviour. Abstract : Heterobiaryls containing a quaternized nitrogen within a chiral N − C axis occur in Nature and have been the target of several total syntheses. Here we reveal a general methodology towards enantio‐enriched N ‐arylquinolinium salts, obtained via a four‐step route from commercially available precursors and with axial stereochemistry controlled through an enantioselective ring‐closing Buchwald–Hartwig coupling reaction.